Pelanggaran Penggunaan Karya Berlisensi Creative Commons dalam Perspektif UUHC dan UU ITE : Penelitian - Rizkita, Indri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This research aims to analyze the legal protection for creators regarding the use of Creative Commons-licensed works under the Indonesian Copyright Law (Law No. 28 of 2014) and the Electronic Information and Transactions Law as amended by Law No. 1 of 2024. In practice, Creative Commons licenses are often misunderstood as a complete waiver of copyright. However, violations of license terms, such as failure to provide attribution or unauthorized commercial use remain legally enforceable. This study uses a normative juridical method with statutory, conceptual, and case-based approaches. The findings indicate that Creative Commons licenses are legally recognized as valid non- exclusive agreements under Indonesian law. Legal protection for creators is enforced both preventively and repressively, while the synergy between Copyright Law and ITE Law forms a comprehensive legal framework for addressing copyright infringements in the digital realm